LEARNING STRATEGIES FOR ISLAMIC RELIGIOUS EDUCATION IN THE FAMILY TO INCREASE CHILDREN'S SPIRITUAL AWARENESS - Muhammad Munif (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Families play a very important role in shaping children's spiritual awareness by having a great responsibility in guiding children to understand the teachings of Islam. Children's spiritual awareness is strengthened through a family environment that supports spiritual growth and strengthens the bond between children and God. By integrating religious routines into daily life, families shape spiritual awareness that is integrated into children's daily activities. The role of the family includes not only conveying information about religious teachings, but also involves implementing moral values in every daily behavior, creating an environment that supports the moral and spiritual growth of the child. Although faced with challenges such as cultural changes, lack of parental understanding, technological influences and time pressures, this article encourages the development of learning strategies that are creative, integrated and appropriate to the dynamics of modern family life.